2015
DOI: 10.1007/s11356-015-5251-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of poultry manure on soil biochemical properties in phthalic acid esters contaminated soil

Abstract: This study aimed to evaluate the effects of poultry manure (PM) on soil biological properties in DBP- and DEHP-contaminated soils. An indoor incubation experiment was conducted. Soil microbial biomass C (Cmic), soil enzymatic activities, and microbial phospholipid fatty acid (PLFA) concentrations were measured during incubation period. The results indicated that except alkaline phosphatase activity, DBP and DEHP had negative effects on Cmic, dehydrogenase, urease, protease activities, and contents of total PLF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Phthalate acid esters (PAEs) are a group of nonhalogenated synthetic compounds that are widely applied in building materials, fragrances, plasticizers, and many other customer‐oriented materials . Higher‐molecular‐weight PAEs, such as bis(2‐ethylhexyl) phthalate (DEHP), are widely used as plasticizers in the industry to improve flexibility , while the low‐molecular‐weight phthalates, like dimethyl phthalate (DMP), diethyl phthalate (DEP), di‐ n ‐butyl phthalate (DBP), and butyl benzyl phthalate (BBP) are usually applied to keep the durability of the color or scent in consumable products . Due to the wide use of PAEs, they extensively exist in the environment through migration or evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Phthalate acid esters (PAEs) are a group of nonhalogenated synthetic compounds that are widely applied in building materials, fragrances, plasticizers, and many other customer‐oriented materials . Higher‐molecular‐weight PAEs, such as bis(2‐ethylhexyl) phthalate (DEHP), are widely used as plasticizers in the industry to improve flexibility , while the low‐molecular‐weight phthalates, like dimethyl phthalate (DMP), diethyl phthalate (DEP), di‐ n ‐butyl phthalate (DBP), and butyl benzyl phthalate (BBP) are usually applied to keep the durability of the color or scent in consumable products . Due to the wide use of PAEs, they extensively exist in the environment through migration or evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous indications suggested that dibutyl phthalate could increase soil CAT activity while decreasing soil urease activity [ 47 51 ]. PAEs have also been reported to inhibit soil dehydrogenase and urease activities [ 49 , 51 , 52 ]. In the present study, both exogenous diisooctyl phthalate and dibutyl phthalate could increase the activities of urease, sucrase, and catalase in the rhizosphere of watermelon in continuous cropping systems.…”
Section: Discussionmentioning
confidence: 99%